KIAT MAHASISWA BERKOMUNIKASI DIDALAM BAHASA INGGRIS PASKA PENDEKATAN FRESHNESS DAN ENTHUSIASM - Rusmono, Doddy (Universitas Pendidikan Indonesia, 2014)
AbstractThrough DIMBI (Diskusi Ilmiah Mahasiswa Berbahasa Inggris – Student’s English Discussion) some can be drawn that learners (i.e. Students) want to have their messages accepted in a proper way by the receiver in the target language. By merely integrating vocabulary and grammar to communicate, the meaning of the expression could not reach the intended receiver and might end up with being incomprehensive on his part. Elelments of culture are neede to make other people understand what you are trying to say, especially when the one you are talking to is a native speaker of English language. Learners are in the situation in which English fall into the category of a foreign, and not English as a second language. When learning English as a second language takes place, the learners are involved in the language in their daily life ectivities while learning English as a foreign language as the case in Indonesia, acquisition and usage depend on and are restricted to learning structures as designed for classroom mode with its various impacts. However little any attempts made by the learners, appreciation and good points of view must emerge for the sake of skill developments. Ways of exploring with tricks by the learners everytime they try to communicate in English with a number of mistakesn needs to be ameliorated in such a way that hopes for betterments live a good endeavour. Approach in the light of teacher demeanor brings with it a positive impact. The approach generates freshness and enthusiasm as well and thus encouraging the learners to express with confidencde regardless of possible inaccuracies in their various forms.Keywords: vocabulary, grammar points, communication, culture, target language. AbstrakMelalui DIMBI (Diskusi Ilmiah Mahasiswa Berbahasa Inggris) terperoleh simpulan bahwa para pembelajar (baca: Mahasiswa) ingin agar pesan yang mereka komunikasikan dapat berterima. Dengan menggabungkan kosa-kata dan gramatika saja pesan yang mereka sampaikan sebagai penutur belum cukup untuk memenuhi keberterimaan oleh penerima pesan pada bahasa sasaran (Bahasa Inggris). Diperlukan unsur kultur untuk mencapai bahasa sasaran. Unsur kultur akan sangat menentukan makna yang ditangkap oleh penerima pesan, terutama bilamana penerima pesan tadi adalah penutur asli (native speaker). Pembelajar berada dalam situasi yang dikategorikan Bahasa Inggris sebagai Bahasa Asing (English As A Foreign Language) , bukan sebagai Bahasa Kedua (English As A Second Language). Ketika bergagas melalui ujaran didalam Bahasa Inggris sebagai bahasa kedua, pembelajar dilibatkan dengan bahasa ini didalam kehidupan sehari-hari mereka sedangkan pembelajaran Bahasa Inggris sebagai bahasa asing seperti misalnya di Indonesia, perolehan dan penggunaan Bahasa Inggris tergantung dan terbatas pada rancangan belajar di ruang kelas dengan segala dampak penyertanya. Upaya sekecil apapun oleh pembelajar harus dilihat dari segi positifnya untuk kemudian dicarikan cara pengembangannya. Kiat penuh kekeliruan sekalipun perlu dihidupkan agar komunikasi tetap berlangsung lancar dan berterima. Pendekatan melalui teacher demeanor yang menyegarkan dan penuh semangat membawa dampak positif bagi pembelajar berupa keberanian berekspresi, terlepas dari ketidakpasan disana-sini.Kata kunci: kosa kata, gramatika, komunikasi, kultur, bahasa sasaran.